(untitled) (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2019)
Introduction: Worm infections will affect the intake, digestion, absorption, and metabolism of food. Worm infection can cause nutritional deficiencies in the form of calories, protein, and vitamins and blood loss which results in a decrease in endurance and cause disruption to child development. Objective: This study aims to describe the incidence of helminthiasis (soil transmitted helminth), intake of vitamin B12 and vitamin C in primary school-aged children in Makassar City. Materials and Methods: The type of research used is descriptive. Sampling was carried out using proportional random sampling with a sample of 88 people in Makassar City representing the Manggala District area namely SD Borong Jambu III Inpres and SD Inpres Perumnas Antang II / I and Tallo District namely Rappokalling 67 Elementary School and Kaluku Bodoa Inpres Elementary School. Data collection on children’s characteristics was carried out by interviewing questionnaires and intake using a 2 × 24 hour food recall method, worm examination performed with the Kato Katz technique. Descriptive analysis was carried out using the SPSS application. Results: A total of 15.9% of children had helminthiasis. Children who were positive for helminthiasis were more prevalent in male sexes, namely (22.9%) aged 10 years as much (17.6%) and living in coastal areas as much (23.3%). Vitamin B12 intake showed more children who had more helminthiasis with adequate vitamin B12 intake which was as much as (85.7%). Whereas the status of helminthiasis based on vitamin C intake shows that children who are positive have more worms with less vitamin C intake which is as much as (100%). Conclusions and Suggestions: Suggestions for the community, especially mothers and children, to maintain home environmental sanitation, as well as the importance of consuming nutritious food